2021
DOI: 10.1021/acsami.0c20652
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Cellulose Nanocrystals into Graphene Oxide Membranes for Efficient Antibiotic Removal at High Nutrient Recovery

Abstract: Two-dimensional (2D) material-based membranes hold great promise in wastewater treatment. However, it remains challenging to achieve highly efficient and precise small molecule/ion separation with pure 2D material-fabricated lamellar membranes. In this work, laminated graphene oxide (GO)–cellulose nanocrystal (CNC) hybrid membranes (GO/CNC) were fabricated by taking advantages of the unique structures and synergistic effects generated from these two materials. The characterization results in physiochemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…For the pristine GO membrane, the peaks at 1724, 1642, 1404, 1234, and 1070 cm –1 corresponded to the CO stretching vibration over the −COOH group, the sp 2 -hybridized CC stretching vibration, the C–OH stretching vibration over the −COOH group, the C–O–C stretching vibration, and the C–O stretching vibration over the alkoxyl group. These adsorption bands could be ascribed to the presence of carboxyl, aromatic, epoxy, and alkoxy groups on the GO nanosheets. ,, Compared with the GO-MPD membrane, the adsorption peak intensities of the CO stretching vibration (1728 cm –1 ), the C–OH stretching vibration (1404 cm –1 ), and the C–O–C stretching vibration (1233 cm –1 ) were decreased, which showed that MPD consumed part of the oxygen-containing groups on GO nanosheets through the covalent cross-linking reaction. At the same time, the adsorption band of the CO stretching vibration slightly blue-shifted from 1724 to 1728 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…For the pristine GO membrane, the peaks at 1724, 1642, 1404, 1234, and 1070 cm –1 corresponded to the CO stretching vibration over the −COOH group, the sp 2 -hybridized CC stretching vibration, the C–OH stretching vibration over the −COOH group, the C–O–C stretching vibration, and the C–O stretching vibration over the alkoxyl group. These adsorption bands could be ascribed to the presence of carboxyl, aromatic, epoxy, and alkoxy groups on the GO nanosheets. ,, Compared with the GO-MPD membrane, the adsorption peak intensities of the CO stretching vibration (1728 cm –1 ), the C–OH stretching vibration (1404 cm –1 ), and the C–O–C stretching vibration (1233 cm –1 ) were decreased, which showed that MPD consumed part of the oxygen-containing groups on GO nanosheets through the covalent cross-linking reaction. At the same time, the adsorption band of the CO stretching vibration slightly blue-shifted from 1724 to 1728 cm –1 .…”
Section: Results and Discussionmentioning
confidence: 96%
“…In addition, the composite membranes prepared by doping are also a way to improve the performance of nanofiltration. Gao et al prepared the hybrid membrane by mixing GO with cellulose nanocrystal (CNC) and loading it on a poly­(vinylidene fluoride) (PVDF) substrate, which had a unique structure and synergistic effect, and showed high water permeability and antibiotic rejection rate . Zhang et al prepared a partially reduced graphene oxide (prGO)-doped sulfonated graphene oxide (S-GO) composite membrane and carried out thermal deoxidation treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, fluorescence detection has been widely applied to detection of antibiotics because of its facile operation and high sensitivity . In addition, various techniques for removing antibiotics from water involve catalysis, adsorption, membrane separation, etc. In water pollution control, catalysis treatment has also been recognized as a convenient and efficient method . Among the various reactions, photocatalytic water purification has attracted a lot of attention because of its high efficiency, low cost, and easy operation .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, nCL/GO composites were applied to develop sensors, capacitors, , water treatment membranes, , biomaterials, and environmental remediation materials . The GO functional groups (i.e., hydroxyl, epoxy, carbonyl, and carboxyl) favor the electrostatic attraction and hydrogen bonding with cellulose chains .…”
Section: Introductionmentioning
confidence: 99%